Psoriasis-associated vascular disease: The role of HDL - Paiva-Lopes, M.J. (2017)
Psoriasis is a chronic inflammatory systemic disease with a prevalence of 2-3%. Overwhelming evidence show an epidemiological association between psoriasis, cardiovascular disease and atherosclerosis. Cardiovascular disease is the most frequent cause of death in patients with severe psoriasis. Several cardiovascular disease classical risk factors are also increased in psoriasis but the psoriasis-associated risk persists after adjusting for other risk factors. Investigation has focused on finding explanations for these epidemiological data. Several studies have demonstrated significant lipid metabolism and HDL composition and function alterations in psoriatic patients. Altered HDL function is clearly one of the mechanisms involved, as these particles are of the utmost importance in atherosclerosis defense. Recent data indicate that biologic therapy can reverse both structural and functional HDL alterations in psoriasis, reinforcing their therapeutic potential. © 2017 The Author(s).